Radiological aspects during cutting and removal of L-08 coolant channel from the core of 540 MWe TAPS-4 nuclear reactor - Durgaprasad Dakinedi (Wolters Kluwer Medknow Publications, 2021)
The pressurized heavy-water reactors (PHWR) consist of a low-pressure horizontal reactor vessel, calandria, containing heavy water as moderator. The calandria is pierced by a large number of coolant tubes (also called pressure tubes [PTs], 392 in 540 MWe PHWR), which contains fuel bundles, and through which pressurized heavy-water coolant circulates. During biennial shut down in 2017, in-service inspection of coolant channels in Tarapur atomic power station-4 (TAPS-4) had been carried out and after the review of results of inspection, it was recommended by various groups of experts that channel L-08 should be removed for postirradiation examination at Bhabha Atomic Research Center (BARC). Before the channel removal job, one special shielding flask was designed to shift the removed channel to BARC. The integrity test of special shielding flask was carried out by safely placing cobalt-60 (source strength 851000 MBq) capsule source inside the shielding flask with the help of cranking unit mechanism followed by dose rate mapping on the outer surface of the flask. To establish the hydrogen pickup rates in L-08 PT, sliver samples were collected and separately sent to BARC. Four metallic sliver samples were obtained at four different distances from north E-face. The activity content present in each sliver sample was also estimated. The maximum activity estimated was 2313.24 MBq. Subsequently, L-08 coolant channel was cut from both sides using a chipless tool. Jobs involving heavy water (D2O) collection work were carried out with a ventilated plastic suit. Derived air concentration (DAC) of tritium at the work location was maintained below 1DAC during the entire activity. Particulate DAC was found below the detectable limit. Floor contamination checks and floor decontamination were conducted at regular intervals to avoid buildup of contamination. As a result of such high-quality radiological safety measures, only 25 workers, out of 270 radiation workers, have received a cumulative dose of more than 3 mSv in direct reading dosimeter with a maximum individual dose of 8.45 mSv and maximum individual uptake of 0.39 GBq/m3. Job was completed with a total collective dose of 324.35P-mSv which is 14.5% lower than estimated. This article highlights some of the critical tasks involved in the cutting and the removal of irradiated coolant channel from the core of 540 Mwe TAPS-4 reactor which is a first of kind activity in nature.